Evaluative Judgment: A Validation Process to Measure Teachers’ Professional Competencies in Learning Assessments - José Miguel Olave Astorga; Félix González-Carrasco (Education Sciences)
This article deals with teachers’ professional development, focusing specifically on their competencies to assess learning. Research in this field has shown a lack of instruments for measuring such competencies in practicing teachers. In this context, we present the validation process of such an instrument, called Classroom Evaluative Judgment, which is designed to assess teachers’ competencies in evaluating their students’ school work. We adopt a quantitative approach, with a non-experimental and sequential design. First, the instrument was subjected to content validation through expert judgment. Subsequently, a pilot test was carried out with an unintentional sample, applying statistical reliability analysis and confirmatory factor analysis to ensure the internal consistency of the instrument with respect to its theoretical basis. Finally, we validated the instrument with 266 participants, obtaining high levels of internal consistency and statistical reliability. The results support the soundness of the proposed model and its usefulness for measuring professional teaching competencies in the field of learning assessment. Its application in real contexts of professional practice could open new lines of research on the evaluative judgment of teachers and the strengthening of their evaluative identity.